Adoção internacional: uma possibilidade de inclusão familiar - Kistemann, Flávia Aparecida (2008)
This thesis is entitled International Adoption: a feasible family inclusion procedure and is aimed at approaching and analysing international adoption as a feasible social and family inclusion procedure guaranteed by law. International adoption has always been the last resort as regards protective measures towards children and adolescents who have been deprived of family connections and only in exceptional cases has been used to provide Brazilians with both social and family interactions. Adoption by foreigners is a specific legal solution which can be advantageous to Brazilian children as long as national and international legislations and procedures are observed. Its application is guaranteed by The Child and Adolescent Statute (ECA) and is ratified by the Hague Convention. This study provides a historical record of international adoption in Brazil and the profile of the potential foreign adoptive parents, who seek their children in the state of São Paulo. The study also comprised interviews with professionals in this area, whose comments showed the need for an international adoption agency which offers children possibilities of family inclusion as well as the need for revised adoption procedures so that a broader number of children and adolescents can find a family of their own and international adoption can no longer be considered the last and single resort